Recurrent squamous cell carcinoma of head and neck: results of treatment in the Chelyabinsk Regional Clinical Center of Oncology and Nuclear Medicine in 2012–2016 - R. Yu. Karabut; A. V. Vazhenin; E. Y. Mozerova; T. M. Sharabura; M. M. Sarycheva; A. O. Guz; A. S. Zakharov (Опухоли головы и шеи, 2020)
Introduction. There is no treatment for recurrence of head and neck squamous cell carcinoma, which significantly increases the overall survival (OS) of patients.The study objective is to analyze the results of treatment of patients with recurrences of squamous cell carcinoma of the head and neck and to assess the impact of risk factors for relapse, as well as different treatment options for relapse on OS. Materials and methods. In the period from 2012 to 2016, 182 patients with relapses of squamous cell carcinoma of the larynx, oral cavity and tongue received treatment in the Chelyabinsk regional clinical center of Oncology and nuclear medicine. The group 1 included 66 patients with resectable relapse who were operated. The group 2 consisted of 25 patients who received a course of radiation therapy. The group 3 consisted of 46 patients who underwent chemotherapeutic treatment of relapse. The group 4 was represented by combined treatment (surgery + radiation therapy), this group included 9 people. The group 5 consisted of those of patients who were not specifically treated for relapse because of the low Karnofsky index in patients (<70 %). Results. OS among patients who received special treatment was significantly higher compared with the group of symptomatic therapy. The median OS in the special treatment group was 40 months, and without it – 18 months. Comparing all types for treating relapse, the highest rates of OS were in the surgical treatment group. OS rates in combined therapy group and radiotherapy group were comparable rate in the radiotherapy. The lowest OS rate was after chemotherapy (only 21 months).Conclusion. Surgery is the optimal method for treating recurrent squamous cell carcinoma of head and neck, if it is resectable. If surgical treatment is not possible, no other method significantly increases the OS. If the overall status of the patient is normal, re-radiation or polychemotherapy may be performed. A limited category of patients can be subjected to combined treatment for relapse.